Protection of Victims of Cybercrime in the Era of Industrial Technology 4.0 - Swardhana, Gde Made; Purwani, Sagung Putri M.E.; Kelly, Danial (Law, State and Telecommunications Review, 2025)
[Purpose] To ascertain and examine the legal protection available to victims of cybercrime in the context of the advent of Industrial Technology 4.0. [Methodology/approach/design] This paper employs a normative legal research method, utilising a literature study approach to examine the relevant laws, books and journals pertaining to this study. In Indonesia, positive law regulates all acts that are considered deviant and in need of legal regulation, including cybercrime. The prevalence and diversity of cybercrime are on the rise, with perpetrators targeting an increasing number of victims. [Findings] Legal protection for victims of cybercrime in the context of industrial technology 4.0 is enshrined in various legislative instruments. Nevertheless, despite this legal framework, the evolving nature of cybercrime necessitates a more robust approach to ensure that victims are adequately safeguarded.